2005
DOI: 10.1111/j.1540-6520.2005.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Comparison of the Behavioral Dynamics of Top Management Teams in Family and Nonfamily New Ventures: Cohesion, Conflict, Potency, and Consensus

Abstract: While some researchers propose that the combination of family and business creates a need for trade-offs in family and business demands, we argue that the social system of the family creates a synergy in the top management team (TMT) that is not present in TMTs with less "familiness." We argue that the unique dynamics created by the social aspects of the familyowned firm will result in higher cohesion, potency, task conflict, and shared strategic consensus than those TMTs with less "familiness." Discriminant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
282
3
15

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(320 citation statements)
references
References 73 publications
5
282
3
15
Order By: Relevance
“…Although previous research has highlighted that some conflicts, such as task and process conflicts, may have positive effects for sustainability Eddleston 2004, 2007), empirical studies have confirmed that relationship conflicts hamper the functioning of the family business Ensley and Pearson 2005). Family firms are fertile grounds for such conflicts (Boles 1996;Miller and Rice 1988;Swartz 1989) because divergent groups may pursue competing goals (Gersick et al 1997).…”
Section: The Role Of Family Ownership In International Entrepreneurshipmentioning
confidence: 99%
“…Although previous research has highlighted that some conflicts, such as task and process conflicts, may have positive effects for sustainability Eddleston 2004, 2007), empirical studies have confirmed that relationship conflicts hamper the functioning of the family business Ensley and Pearson 2005). Family firms are fertile grounds for such conflicts (Boles 1996;Miller and Rice 1988;Swartz 1989) because divergent groups may pursue competing goals (Gersick et al 1997).…”
Section: The Role Of Family Ownership In International Entrepreneurshipmentioning
confidence: 99%
“…Accordingly, 160 usable and completed responses from 40 TMTs were included in the final dataset [13] (4 TMT member from 40 SMEs). Considering previous studies conducted in the TMT context, our sample size was within the acceptable range of 20-100 teams [5,13,29,34,53,[75][76][77][78].…”
Section: Methodsmentioning
confidence: 99%
“…After all, family businesses, by definition, are founded and led by teams rather than by individuals, and these teams are responsible for the development and implementation of the firm's decisions. As noted by Ensley and Pearson (2005), "it is within this complex web of social involvement and interactions embedded in the social structure of the family that the advantages of the family firm can be identified" (p. 268). Management teams in family businesses can consist of multiple family, or perhaps nonfamily, members (Cater & Justis, 2010).…”
Section: Teams and Family Businessesmentioning
confidence: 99%